Handedness throughout the lifespan: cross-sectional view on sex differences as asymmetries change - Sivagnanasunderam, Mukundhan; Gonzalez, Dave A.; Bryden, Pamela J.; Young, Gordon; Forsyth, Amanda; Roy, Eric A. (Frontiers in Psychology, 2015)
Manual asymmetries has been studied by many researchers, however contradictory findings still exist as to whether preferred manual asymmetries increases with age or do we become more ambidextrous. Recently it was shown that perhaps there is a third option, that there is no increase or decrease in laterality but rather preferred manual asymmetries remains consistent throughout adulthood. Another related finding is that females appear to have an advantage in some handedness tasks, such as the Grooved Pegboard. When a larger pegboard is used, sex differences may reverse as males may perform better when larger pegs and a larger trajectory are required. However, it is not fully understood if these sex differences arise from an early age and continue throughout life. Therefore we sought to explore sex differences in preferred hand dominance throughout the lifespan. In order to explore preferred hand dominance during the lifespan we examined 76 children (19 4 to 5 year olds, 12 female, M age = 4.73; 34 6 to 8 year olds, 12 female, M age = 6.97; 23 9 to 12 year olds, 14 female, M age = 10.83) in Experiment 1 and 35 healthy young right-handed adults (15 female, M age = 20.91) and 37 healthy older right-handed adults (20 female, M age = 72.3) in Experiment 2. Individuals were tested using a standard size (small) and modified Grooved Pegboard (larger pegboard). Our study demonstrates that hand asymmetries are present early in life (children 4 to 5 years old) at that these differences attenuate as a function of age until adulthood (Experiment 1). Furthermore, our results demonstrate that as we age (Experiment 2), asymmetries may increase (small and large pegboards), decrease (Annett), or stay the same (finger tapping). As well we demonstrated that the sex differences could not be entirely accounted for by hand size. Therefore, asymmetries as regard to the aging process, seems to be task specific which may account for the conflicting findings in research.